Strengthening Interactive Dental Health Education for Early Childhood in the Era of Globalization - Kristianto, Jusuf; Pasaribu, Roben Suhadi; Muliawati, Dian (International Journal Labs, 2025)
Dental health education is a crucial preventive measure in shaping healthy lifestyle behaviors from an early age. The success of education depends not only on the content of the material, but also on the effectiveness of the media and methods used to convey the message in an interactive and easily understandable way to children. This study aims to determine the changes in the index before and after education on how to brush teeth at Global Mandiri Kindergarten. This was a pre-experimental study with a one-group pretest–posttest design involving a total sample of 57 kindergarten B students. The intervention consisted of education on the purpose of brushing teeth, choosing the right toothbrush, brushing techniques (roll technique), brushing duration, and the use of fluoride toothpaste. The debris index was examined before and after the interactive education with the Playstore GigiKuHartaKu program. Results: Examination before the education showed a moderate to poor debris index category. After the intervention, there was a change in the debris index category to good and moderate. There was a significant decrease in the debris index from 2.11 to 0.711, with a p-value of 0.001 (p<0.05). Conclusion: The intervention, in the form of interactive and structured dental education, significantly improved dental hygiene in young children. These findings reinforce the importance of promotional education in the school environment as the foundation for long-term healthy living behaviors.